2021
DOI: 10.1158/0008-5472.can-20-1674
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efficacy of Simultaneous PD-1 and PD-L1 Immune Checkpoint Blockade in High-Grade Serous Ovarian Cancer

Abstract: Competing interests: M.B. receives sponsored research support from Novartis. M.B. serves as a consultant and scientific advisor to Kronos Bio, H3 Biomedicine and GV20 Therapeutics. In the past M.B. served as a scientific advisor to GTx, Inc. and as consultant to Aleta BioTherapeutics. U.A.M. is a consultant for Novartis and Merck, is on the scientific advisory boards for 2X Oncology and the Clearity Foundation, and is an uncompensated advisor for AstraZeneca. X.S.L. is a cofounder and board member of GV20 Onco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 54 publications
0
124
0
Order By: Relevance
“…The prospect of more complex organoid models also encompassing immune, stromal and/or vascular cells, raises the hope to in the future test clinically relevant drugs that tackle neo-angiogenesis and tumor immunology. Indeed, shortterm 3D spheroid co-cultures of HGSOC cells with immune cells have shown sensitivity to immune checkpoint inhibitors (Wan et al, 2020).…”
Section: Ovariesmentioning
confidence: 99%
“…The prospect of more complex organoid models also encompassing immune, stromal and/or vascular cells, raises the hope to in the future test clinically relevant drugs that tackle neo-angiogenesis and tumor immunology. Indeed, shortterm 3D spheroid co-cultures of HGSOC cells with immune cells have shown sensitivity to immune checkpoint inhibitors (Wan et al, 2020).…”
Section: Ovariesmentioning
confidence: 99%
“…Moreover, scRNA-seq has been used to develop gene-expression-signature of the myeloid-derived suppressor cells (MDSCs) in addition to identifying CD84 as a surface biomarker for MDSCs in breast cancer [ 202 ]. Similarly, Wan et al reported reprogramming of inert natural killer and T cells to a highly active cytotoxic state following bispecific anti-PD-1orPD-L1 antibody treatment using single-cell RNA-seq analysis of HGSOC organoid co-cultures; this study identified a potential advantage of bispecific antibodies in immune checkpoint blockade therapy in HGSOC [ 203 ]. Further analyses have identified inter- and intra-tumor heterogeneity in cancer associated fibroblasts cell states in HGSOC and breast cancer [ 117 , 204 ].…”
Section: Advances In Genomic Analyses Of Breast and Ovarian Cancermentioning
confidence: 98%
“…Nevertheless, one limitation of PDOs is currently represented by the lack of reliable protocols capable to faithfully reproduce the tumor microenvironment, which comprises the stroma, immune cells and blood vessels [6,[8][9][10][67][68][69][70][71][72][73][74]. However, the recent development of organoids cocultured with tumor microenvironment components holds promise for the possibility to evaluate complex features of tumors in the near future [76,77]. Short term PDO cultures were recently shown to maintain tumor infiltrating immune cells and have been successfully employed for comparative analyses of immune checkpoint therapies responses [77].…”
Section: Patient-derived Organoidsmentioning
confidence: 99%
“…However, the recent development of organoids cocultured with tumor microenvironment components holds promise for the possibility to evaluate complex features of tumors in the near future [76,77]. Short term PDO cultures were recently shown to maintain tumor infiltrating immune cells and have been successfully employed for comparative analyses of immune checkpoint therapies responses [77]. Moreover, in cancers characterized by a high tumor mutational burden, coculture of PDOs with peripheral blood lymphocytes generated CD8+ T cell clones specifically reactive against neoplastic cells, thus potentially valuable for adoptive cell transplantation [78].…”
Section: Patient-derived Organoidsmentioning
confidence: 99%